Unions and Collective Bargaining : Economic Effects in a Global Environment. - Aidt, Toke (Directions in development (Washington, D.C.), 2002)
This book offers an extensive survey and synthesis of the economic literature on trade unions and collective bargaining and their impact on micro-and macro-economic outcomes. The authors demonstrate the effects of collective bargaining in different country settings and time periods. A comprehensive reference, this book will be of interest to students and scholars of labor policy as well as to policy makers and anyone with an interest in the economic consequences of unionism.